2010
DOI: 10.1002/dmrr.1133
|View full text |Cite
|
Sign up to set email alerts
|

Evolution and predictors of morphological and functional arterial changes in the course of type 1 diabetes mellitus

Abstract: There are differences in the time course of evolution and in predictors of morphological and functional changes in arteries in type 1 diabetes mellitus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 39 publications
1
12
0
2
Order By: Relevance
“…Recently, structural changes in the carotid arteries of type 1 diabetics without overt vascular disease were examined according to age and the duration of diabetes [9]. The researchers found that intima-media thickness was one of the first parameters to change in the diabetic population.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, structural changes in the carotid arteries of type 1 diabetics without overt vascular disease were examined according to age and the duration of diabetes [9]. The researchers found that intima-media thickness was one of the first parameters to change in the diabetic population.…”
Section: Discussionmentioning
confidence: 99%
“…Several factors are important in predicting the advancement of aortic dysfunction in people with diabetes. Age is one of the most important, as it is an independent predictor of stiffness and pulse wave velocity [9]. In addition, the duration of diabetes predicts the intima-media cross-sectional area and systolic blood pressure [9].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Yavuz et al (26) and Gunczler et al (27) found no increase of CA-IMT in children with type 1 DM. However, Yamasaki et al (28) Jarvisalo et al (29) and Vastagh I et al (30) reported that CA-IMT values were significantly higher in children with type 1 DM. Jarvisalo et al (29) also showed that type 1 DM was an independent risk factor for high CA-IMT.…”
Section: Discussionmentioning
confidence: 97%